Urban Rituals in Sacred Landscapes in Hellenistic Asia Minor - Williamson, Christina G., (Religions in the Graeco-Roman World ;, 2021)
In Urban Rituals in Sacred Landscapes in Hellenistic Asia Minor , Christina G. Williamson examines the phenomenon of monumental sanctuaries in the countryside of Asia Minor that accompanied the second rise of the Greek city-state in the Hellenistic period. Moving beyond monolithic categories, Williamson provides a transdisciplinary frame of analysis that takes into account the complex local histories, landscapes, material culture, and social and political dynamics of such shrines in their transition towards becoming prestigious civic sanctuaries. This frame of analysis is applied to four case studies: the sanctuaries of Zeus Labraundos, Sinuri, Hekate at Lagina, and Zeus Panamaros. All in Karia, these well-documented shrines offer valuable insights for understanding religious strategies adopted by emerging cities as they sought to establish their position in the expanding world.